Fundamental Rights and Taxation: The Fight Against Social Inequality in tThe 2008 Post-Crisis Scenario - Taisa Vieira Scripes; Nicholas Lima Barbosa Mendes (Revista Brasileira de Direitos e Garantias Fundamentais, 2016)
The globalization and the crisis of 2008 make difficult to achieve basic guarantees such as human dignity (Art. 1, III, CF/88), the guarantee of property rights (art. 5, XXII) and the rights to education, health, work and housing (art. 6, caput). At the post-crisis context, where social inequality increased, the taxation can help to achieve such guarantees. However, when analyzing the national tax system, using data supplied by the federal government, it is possible to realize that the system has a logic contrary to the fundamental guarantees provided in the Constitution.